Triazine derivatives as organic phase change materials with inherently low flammability. Issue 7 (20th January 2022) - Png, Zhuang Mao; Soo, Xiang Yun Debbie; Chua, Ming Hui; Ong, Pin Jin; Xu, Jianwei; Zhu, Qiang
Abstract : A series of triazine-based compounds (M1–M7 ) have been prepared from 1, 3, 5-triazine, 2, 4, 6-triamino-1, 3, 5-triazine, 2, 4-dichloro-6-methoxy-1, 3, 5-triazine and 2-chloro-4, 6-dimethoxy-1, 3, 5-triazine, and their thermal phase change properties. Abstract : A series of triazine-based compounds (M1–M7 ) have been prepared starting from 1, 3, 5-triazine, 2, 4, 6-triamino-1, 3, 5-triazine (melamine), 2, 4-dichloro-6-methoxy-1, 3, 5-triazine and 2-chloro-4, 6-dimethoxy-1, 3, 5-triazine via either alkylation or amidation, and their thermal phase change properties were studied. Depending on the functional group introduced, the melting point of these 1, 3, 5-triazine derivatives ranged from 43 °C to 190 °C, while the enthalpy change of melting ranged from 47 to 150 J g −1 . Vertical burning tests showed that most of these compounds required a lower amount of flame retardants to achieve self-extinguishing properties as compared to paraffin. Cone calorimetry studies of compound M1 showed that the peak heat release rate (pHRR) is reduced by about 30% from 1908 (for a paraffin/malamine (23%) blend) to 1359 kW m −2, while the average heat release rate is lowered by about 25% from 854 to 655 kW m −2 . These studies indicate that triazine derivatives can serve as intrinsically flame-retardant phase change materials and partially address the flammability issue of existing organic phase change materials. This also demonstrates the superiority of chemical bonding as a means of introducing flame retardants as compared to physical blending.